ANALISIS KINERJA PEMASARAN PADA INDUSTRI MAKANAN (Studi Kasus UMKM CV. NJ Food Industries, Kabupaten Sukabumi) - Sopyan Saori; Deya Mentari Octavia Anugerah; Anak Agung Putu Ayu; Ibrohim Ibrohim; Kholipah Al Mugni (Sekolah Tinggi Pariwisata Mataram, 2021)
This study aims to see whether the marketing performance carried out by UMKM CV. NJ Food Industries is optimal. The research was conducted at UMKM CV. NJ Food Industries. The method used in this journal is descriptive analysis method. The data obtained through the measurement of financial metrics is really to calculate how the profitability and marketing costs are obtained through interviews with the owner of the UMKM CV. NJ Food Industries. The objectives achieved in this study include: seeing the marketing performance of CV. NJ Food Industries in its business organization with the hope of helping the progress of Micro, Small and Medium Enterprises (MSMEs)